Exposure Profile and Characteristics of Parabens and Alkylphenols in Plasma among Rural Adults in Central China - Qian Gao; Changsheng Huan; Yu Song; Zexin Jia; Qingqing Cao; Chongjian Wang; Zhenxing Mao; Wenqian Huo (Toxics, 2023)
Parabens and alkylphenols pose serious hazards to human health, yet there are few studies on their exposure profiles and health risks in rural Chinese populations. In this study, 804 participants were selected from the Henan Rural Cohort in mid-eastern China. The plasma levels of parabens (methylparaben, ethylparaben, propylparaben, butylparaben (BuP)) and alkylphenols (4-tert-butylphenol (4-t-BP), 4-tert-octylphenol (4-t-OP)) were analyzed via liquid chromatography–tandem mass spectrometry. Linear regression models were used to investigate factors that may influence pollutant exposure levels. The correlation between contaminants was assessed using Spearman’s correlation. The human contaminant intake was estimated using the estimated daily intake (EDI). The health risk was assessed using the hazard quotient (HQ). The detection frequency of four parabens and two alkylphenols exceeded 75%, with median concentrations of 0.444, 0.067, 0.078, 0.053, 8.810, and 6.401 ng/mL, respectively. Significant correlations were observed between parabens, as well as between 4-t-BP and 4-t-OP. Regarding gender, paraben concentrations were higher in women than in men, except for BuP. The EDI for pollutants except 4-t-OP was lower than their respective tolerable/acceptable daily intake. In total, 85.70% of participants had 4-t-OP HQ > 1. A widespread exposure to parabens and alkylphenols among the rural population was found. The high health risks of alkylphenol exposure indicate that alkylphenols should be used with caution.